Writing a thesis in the era of ChatGPT: The lived experiences of PhD international students at UK universities - Karmi, Karim (Journal of International Students, 2026)
This study explores the thesis-writing experiences of international PhD students in UK universities, with particular attention to the challenges they encounter and their use of ChatGPT as an academic writing support tool. Drawing on qualitative data from semi-structured interviews with 19 international doctoral students across four UK institutions, the study employs thematic analysis using NVivo to examine both writing practices and perceptions of AI-assisted tools. The findings indicate that the primary challenges are not linguistic but cognitive and rhetorical in nature, including difficulties with idea development, structuring coherent arguments, engaging in critical analysis, and articulating an academic voice. Participants generally viewed ChatGPT as a useful tool, particularly for editing and brainstorming; however, they also expressed concerns about its potential long-term effects on independent thinking and academic writing development. Uncertainty regarding the ethical boundaries of AI use, especially in relation to academic integrity, further complicated their engagement with the tool.